Keanekaragaman dan Distribusi Gastropoda Air Tawar di Sungai Ciapus, Jawa Barat, Indonesia: Diversity and Distribution of Freshwater Gastropods in Ciapus River, West Java, Indonesia - Ayub Wirabuana Putra; Muhammad Al Anshari; Nurul Magfirah Sukri; Tri Heru Widarto; Tri Atmowidi; Magdalena Litaay; Windra Priawandiputra (Jurnal Sumberdaya Hayati, 2023)
Despite being part of food web and bioindicator in freshwater ecosystems, gastropods are globally jeopardized. Therefore, the occurence of freshwater gastropods need to be assessed. This research aimed to examine diversity and distribution of freshwater gastropods along the Ciapus River in Bogor, West Java, Indonesia. The research was conducted from February to May 2020. Sampling was carried out within limited 15 minutes time period using five 1 × 1 m plots established at each of four survey stations. Gastropods were collected from the bottom of river, rock surface and riverbanks within 15-100 cm of water depth. Environmental parameters were recorded. Data was analyzed using biodiversity index parameters and diversity t-test. The survey collected a total 587 individuals from 7 species of freshwater gastropods. The abundance, species richness and diversity of gastropods in the Ciapus river were different between upstream and downstream, location with high altitude tend to have low number of species. Glyptophysa stagnalis became the only species recorded from upstream area. Meanwhile, there were 4 species, which were collected in other three stations and 2 species that recorded from two stations. In three stations, Tarebia granifera was the most dominant species.